2007
DOI: 10.1007/bf03025837
|View full text |Cite
|
Sign up to set email alerts
|

A time line of the evolution of school bullying in differing social contexts

Abstract: These substantial works are typically reflected in the different definitions of bullying and are adapted by other nations where pre-existing theories on bullying have not yet been established. Furthermore, methods of investigating bullying (e.g. selfreports and peer nominations of victimisation), in particular the questionnaire developed by Olweus (1978Olweus ( , 1993, have been widely acknowledged and used in many countries.While not denying the validity of Owleus's questionnaire for investigating bullying, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 19 publications
2
21
0
14
Order By: Relevance
“…The term bullying was rarely used in these accounts, and was instead referred to as a form of interpersonal violence enacted on a daily basis. This suggested that it was an accepted form of behavior, considered “normal” among young people, and seen as an inherent part of human nature for centuries (Koo, ).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…The term bullying was rarely used in these accounts, and was instead referred to as a form of interpersonal violence enacted on a daily basis. This suggested that it was an accepted form of behavior, considered “normal” among young people, and seen as an inherent part of human nature for centuries (Koo, ).…”
Section: Aim Of the Studymentioning
confidence: 99%
“…Systematic study of bullying in schools in the west started in Scandinavia, the first notable publication being Dan Olweus' book, Forskning om skolmobbning (; English translation 1978). In the east, there were studies in Japan and in South Korea at least from the 1980s (Morita, ; Koo, ).…”
Section: History Of Researchmentioning
confidence: 99%
“…Bullying and its impacts on children's lives are long‐standing concerns, with modern research interest emerging in the late 19th century (Burk, ; Koo, ). While descriptions of bullying in earlier work are recognisably consistent with current understandings, the pioneering empirical work undertaken by Olweus () is frequently cited as an originating point for current research literature.…”
Section: Introductionmentioning
confidence: 99%